Sufi's hermeneutic and ITS relevance for contemporary discources on interfaith dialogue ( studies on Ibn al-"Arabi's Hermeneutics and his concept of religious diversity and its applications for interfaith dialogue) - Syafaatun Almirzanah (s.n, 2008)
wt.1/ws.c.1